Physiological differences in professional basketball players as a function of playing position and level of play - Sallet, P.; Perrier, D.; Ferret, J. M.; Vitelli, V.; Baverel, G. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The aim of this investigation is to evaluate the physical and physiological characteristics of different first (ProA) and second division (ProB) professional basketball players, and to relate them to playing position and level of play. Methods: A total of 58 players were divided into ProA and ProB groups and were assessed for physical characteristics, maximal treadmill test and a 30 s all-out test. The sample included 22 centers, 22 forwards and 14 guards. Results: Centers were significantly taller and heavier (203.9±5.3 cm and 103.9±12.4 kg) than forwards (195.8±4.8 cm and 89.4±7.1 kg) and guards (185.7±6.9 and 82±8.8 kg) and also had higher body fat percentages than the other groups. Forwards were also significantly taller than guards. Centers presented a lower maximal aerobic velocity (km·h-1) than guards (15.5±1.2 vs 16.8±1.5, P<0.05) on the maximal treadmill test and a lower maximal velocity (rpm) than forwards (156.5±18.4 vs 170.3±18.3, P<0.05) on the 30 s all-out test. V.O2max (ml·min-1·kg-1) was significantly lower for ProA (53.7±6.7) compared to ProB (56.5±7.7) players and the fatigue index on the 30 s all-out test was higher for the ProA group (P<0.05). Conclusion: Many physical differences, most notably size, exist between players as a function of their playing position. But these differences have no relationship to the level of play of professional players. General aerobic capacity is fairly homogeneous between playing position and level of play, even if there are observable V.O2max differences due to inter-individual profiles. On the other hand, anaerobic capacity seems to be a better predictor of playing level even though it is not clear whether such capacity comes from specific training in ProA, or from an initial selection criteria.